2012
DOI: 10.1002/term.1475
|View full text |Cite
|
Sign up to set email alerts
|

Cell bricks-enriched platelet-rich plasma gel for injectable cartilage engineering - an in vivo experiment in nude mice

Abstract: Clinical application of platelet-rich plasma (PRP)-based injectable tissue engineering is limited by weak mechanical properties and a rapid fibrinolytic rate. We proposed a new strategy, a cell bricks-stabilized PRP injectable system, to engineer and regenerate cartilage with stable morphology and structure in vivo. Chondrocytes from the auricular cartilage of rabbits were isolated and cultured to form cell bricks (fragmented cell sheet) or cell expansions. Fifteen nude mice were divided evenly (n = 5) into ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…30 Different from solid scaffold-based tissue engineering, injectable cartilage constructs require fluidity of components and instant establishment of a chondrogenic niche. Zhu et al 18 proved that fragmented chondrocyte macroaggregates (cell bricks) could stabilize the PRP gel efficiently in vivo and support chondrogenesis with stable morphology. 18 In this study, they found that such an injectable complex could support chondrogenesis of bone marrow mesenchymal stem cells (BMSCs) in vivo and demonstrated that such a complete biological graft could meet the requirement of nasal augmentation, thus holding future promise in craniofacial reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…30 Different from solid scaffold-based tissue engineering, injectable cartilage constructs require fluidity of components and instant establishment of a chondrogenic niche. Zhu et al 18 proved that fragmented chondrocyte macroaggregates (cell bricks) could stabilize the PRP gel efficiently in vivo and support chondrogenesis with stable morphology. 18 In this study, they found that such an injectable complex could support chondrogenesis of bone marrow mesenchymal stem cells (BMSCs) in vivo and demonstrated that such a complete biological graft could meet the requirement of nasal augmentation, thus holding future promise in craniofacial reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…18 In addition, BMSCs are capable of promoting angiogenesis through the secretion of GFs, in particular VEGF. 31 Angiogenesis is a crucial event for tissue regeneration 32 and tumor growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To provide injectable, mechanical supportive BMSC aggregate for cartilage regeneration, we developed a chondrocyte brick (CB; fragmented chondrocyte/ECM macroaggregates)‐enriched platelet‐rich plasma (PRP) gel. A previous study showed that mixing chondrocytes with cell bricks/PRP stabilized clots efficiently . In this study, we found that undifferentiated BMSCs could be well mixed with chondrocyte bricks in a PRP gel and self‐assembled into a macroaggregate of a size that can be used clinically.…”
Section: Introductionmentioning
confidence: 66%